2014
DOI: 10.1093/ejcts/ezu473
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls and premature failure of the Freedom SOLO stentless valve

Abstract: The FS stentless valve is safe to implant and shows satisfying mid-term results in our single institution experience. Freedom from SVD and explantation decreased markedly after only 6-7 years, so that patients with FS require close observation and follow-up. Exact sizing, symmetric positioning and observing patient limitations are crucial for optimal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…In two recent reports from Berne, Switzerland [27], the incidence of explants for SVD was considerably high, but in most of them, a clear association between incorrect implantation and need for reoperation could be identified. Oversizing and undersizing are probably the most frequent errors: leaflets are wrinkled at the level of the suture line, with reduced mobility, higher gradients, and irregular coaptation leading to structural failure.…”
Section: Commentmentioning
confidence: 99%
“…In two recent reports from Berne, Switzerland [27], the incidence of explants for SVD was considerably high, but in most of them, a clear association between incorrect implantation and need for reoperation could be identified. Oversizing and undersizing are probably the most frequent errors: leaflets are wrinkled at the level of the suture line, with reduced mobility, higher gradients, and irregular coaptation leading to structural failure.…”
Section: Commentmentioning
confidence: 99%
“…Therefore, better outcomes with the SS stentless valve depend on optimal patient selection and on recognizing its limitations. 8,11) In conclusion, high-risk patients with infective endocarditis accompanied by annular abscess, a small aortic annulus, and those who require concomitant mitral valve surgery and redo AVR may profit from SS stentless valve implantation.…”
Section: Discussionmentioning
confidence: 99%
“…The stentless valve may be more resistant to SVD; however, because it is early in the follow‐up period, this fact cannot be confirmed. It was reported that freedom from the SVD of the Solo valve decreased markedly after only 6 to 7 years; therefore, further, careful observation is required.…”
Section: Discussionmentioning
confidence: 99%